2019
DOI: 10.1055/a-0994-9970
|View full text |Cite
|
Sign up to set email alerts
|

Serum CA 19–9 Level is Correlated to the Clinical Characteristics and Chronic Complications of Patients Newly Diagnosed with Type 2 Diabetes Mellitus

Abstract: Aim This study investigated the relation of serum carbohydrate antigen 199 (CA 19–9) levels to the clinical characteristics and chronic complications of patients newly diagnosed with type 2 diabetes mellitus (T2DM). Methods A total of 371 patients newly diagnosed with T2DM and 133 healthy people with consecutively matched age were compared. The 371 patients with T2DM were divided into four groups by quartiles based on their serum CA 19–9 levels, in which clinical characteristics and chronic complications, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Retrospective studies have suggested an association between type 2 diabetes mellitus and elevated CEA and CA 19-9. 29,30 Our study has several notable limitations. This study was designed as a retrospective cohort study and has an inherent risk of bias, both known and unknown.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Retrospective studies have suggested an association between type 2 diabetes mellitus and elevated CEA and CA 19-9. 29,30 Our study has several notable limitations. This study was designed as a retrospective cohort study and has an inherent risk of bias, both known and unknown.…”
Section: Discussionmentioning
confidence: 96%
“…Retrospective studies have suggested an association between type 2 diabetes mellitus and elevated CEA and CA 19‐9. 29 , 30 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20,21] However, other studies found proteinuria only in 9%, 14%, and 13.5% patients, respectively. [22][23][24] Presently,microalbuminuria is defined as 30 -300mg/24hours (20 -200μg/min) of albumin in the urine is equivalent to 0.46 to 4.6 μmol/24-h. [25] Urine samples should not be taken from patients in diabetic ketoacidosis, hyperosmolar state, or from patients having poor control until adequate glycemic control is established, and should ideally be collected in resting position. A urinary albumin excertion of less than 20μg/min is considered to be normal.…”
Section: Discussionmentioning
confidence: 99%
“…• Diabetes mellitus is associated with increased CA19-9 values, particularly if metabolic control is poor. 121 Higher cut-off values have also been proposed.…”
Section: Screening (Asymptomatic Subjects)mentioning
confidence: 99%